Evaluation of the South American gastropod Heleobia parchappii as test organism in cadmium toxicity bioassays - Achiorno, Cecilia Luján (2023)
Gastropods are abundant key components in freshwater ecosystems, many of which are affected by anthropogenic activities. The genus Heleobia is widely distributed across Argentina, and the native Heleobia parchappii is very common in the Pampean Region. The identification of native candidate species for toxicity testing is gaining increasing interest. The objectives of the present study were to evaluate 1) the susceptibility of H. parchappii to a reference toxicant (Cl₂ Cd), and 2) its suitability for toxicity testing by estimating LC50. Also, we discussed the applicability of the proposed protocol. Snail sensitivity was assessed by exposure to concentrations between 0.5 and 12 mg Cd/L under acute static conditions during 72 h (exposure period). Then, snails were transferred to the control medium for 24 h (post-exposure period) and checked for recovery and those not responding to stimulation were considered to be dead. The endpoints were snail immobilization (recorded every 24 h during the exposure period) and mortality at the end of the post-exposure period. Snail sensitivity was analyzed with a generalized linear mixed model (GLMM) and LC₅₀ (lethal concentration 50%) was calculated using probit analysis. Results indicated that the number of immobilized snails increased with increasing concentration. The toxic effect of Cd on snails persisted 24 h after exposure. The LC₅₀ was 2.145 (1.675-2.641) mg Cd/L. The sensitivity of H. parchappii was similar to that reported for other freshwater standard species, supporting its suitability as test organism. The protocol was appropriate for use in toxicity testing as it is simple, inexpensive and reproducible.